Abusos de posición dominante en mercados digitales: ¿Nuevos trucos para un perro viejo? - Tapia Canales, Javier (2022)
This paper summarizes the most recent cases concerning unilateral conduct that have been brought in both the United States and Europe against the so-called “Tech Giants” (Amazon, Google Facebook and Apple). It also shows the regulatory solutions that are being put forward in different jurisdictions to deal with the conducts that have given rise to such cases. These conducts produce a tension that is at the core of today’s competition law: whether they are new categories that are not captured by the traditional standard of consumer welfare, or whether they are simply due to characteristics of technological markets that do not produce (new) competition problems.